Community and single cell analyses reveal complex predatory interactions between bacteria in high diversity systems - Yossi Cohen (Nature Portfolio, 2021)
Studying the role of predator–prey interactions in food-web stability and species coexistence in the environment is arduous. Here, Cohen et al. use a combination of community and single-cell analyses to show that bacterial predators can regulate prey populations in the species-rich environments of wastewater treatment plants.